PENTINGNYA PEMAHAMAN ASPEK BUDAYA KONSUMEN DALAM MENGIMPLEMENTASIKAN PROGRAM PEMASARAN - FX Supriyono (Bina Ekonomi, 2003)
This paper discusses about the importance of cultural aspects within the environment. This is mostly important whenever the market goes globally, because the larger market means the most differential taste will be. The differences in cultural background of the consumers cause the differential in consumer's taste. That's why the marketers should consider the cultural aspects of the consumers. Cultural consideration in the marketing programs will create growths of the enterprises because of the acceptance of the products and the acceptance of the way the products are promoted. Therefore, the observations of cultural patterns of the consumers should always be done accurately. By doing the accurate observations, the marketers can designing good decisions about the strategies and the marketing programs.